CUTTNG EDGE ADVERTISING : HOW TO CREATE THE WORLD'S BEST PRINT FOR BRANDS IN THE 21ST CENTURY - Aitchison, Jim, author 278149 (Alexandra Road, Singapore : Prentice Hall)
A hip but not trendy guide to the many angles involved in the creation of print ads. Addresses how advertising works, how brand-building methodologies are changing, how to get an idea, and how copy and art should be crafted. Includes advice from a bevy of advertising masters from the US, UK, Asia.